1994
DOI: 10.1007/bf00023555
|View full text |Cite
|
Sign up to set email alerts
|

The S11 and S13 self incompatibility alleles in Solanum chacoense Bitt. are remarkably similar

Abstract: A genomic clone of the S11 allele from the self-incompatibility locus (S locus) in Solanum chacoense Bitt. has been isolated by cross-hybridization to the S. chacoense S13 allele and sequenced. The sequence of the S11 allele contains all the features expected for S genes of the Solanaceae, and S11 expression, as assessed by northern blots and RNA-PCR, was similar to that of other S. chacoense S alleles. The S11 protein sequence shares 95% identity with the phenotypically distinct S13 protein of S. chacoense an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…Since the pairwise comparisons of the deduced amino-acid sequences detected no completely matching pairs, almost all the Sgenotypes determined by RFLP analysis were expected to reflect the self-incompatibility phenotypes. Two pairs showed high homology, but this does not necessarily mean that their phenotypes were the same, since a small number of amino-acid substitutions appear to be sufficient to trigger the self-incompatibility reaction between the S1/S4 and S3/S5 pairs of Pyrus pyrifolia (Ishimizu et al, 1998), and the S11/S13 pair of Solanum chacoense (Saba-El-Leil et al, 1994). From so few cases it cannot be definitively concluded that a few substitutions are sufficient to express different specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pairwise comparisons of the deduced amino-acid sequences detected no completely matching pairs, almost all the Sgenotypes determined by RFLP analysis were expected to reflect the self-incompatibility phenotypes. Two pairs showed high homology, but this does not necessarily mean that their phenotypes were the same, since a small number of amino-acid substitutions appear to be sufficient to trigger the self-incompatibility reaction between the S1/S4 and S3/S5 pairs of Pyrus pyrifolia (Ishimizu et al, 1998), and the S11/S13 pair of Solanum chacoense (Saba-El-Leil et al, 1994). From so few cases it cannot be definitively concluded that a few substitutions are sufficient to express different specificities.…”
Section: Discussionmentioning
confidence: 99%
“…At least one intron is expected, since the S-alleles of SRNases of Solanaceae and Rosaceae usually have a single intron (in the HVa region, from 87 bp to 120 bp, and 138 bp to 1100 bp, respectively, in sequences from these two families; Saba-El- Leil et al, 1994;Matton et al, 1995;Broothaerts et al, 1995). Prunus (Rosaceae) S-RNases have at least two introns (in P. avium, one 5′ to the C1 region, and one in HVa; Tao et al, 1999), and a sequence from P. dulcis (GenBank accession number AF157008) is similar (Figure 1).…”
Section: Analysis Of a Graniticum Crossesmentioning
confidence: 99%
“…Our experimental system, the tuber-bearing wild potato species S. chacoense , involves two phenotypically distinct S alleles ( S 11 and S 13 ) whose mature proteins differ by only 10 amino acids (Saba-El-Leil et al, 1994), four of which are located in the hypervariable regions ( Figure 1B). We have shown that the substitution of all four of these amino acids in the hypervariable regions of an S 11 RNase with those of an S 13 RNase fully converts the S 11 phenotype into an S 13 phenotype (HVab S RNase; Matton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the gametophytic system, several studies (Clark and Kao, 1991;Coleman and Kao, 1992;Saba-El-Leil et al, 1994;Matton et al, 1995Matton et al, , 1997Ishimizu et al, 1998) have suggested that point mutations rather than intragenic recombination (Fisher, 1961;Pandey, 1970;Ebert et al, 1989) are the primary source of S allele polymorphism. Phenotypically distinct yet highly similar S RNase sequences have been described in Solanum chacoense (Saba-El-Leil et al, 1994) and Pyrus pyriflora (Ishimizu et al, 1998). 1 To whom correspondence should be addressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation